2009
DOI: 10.1073/pnas.0811785106
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting genetic requirements of human breast tumorigenesis in a tissue transgenic model of human breast cancer in mice

Abstract: Breast cancer development is a complex pathobiological process involving sequential genetic alterations in normal epithelial cells that results in uncontrolled growth in a permissive microenvironment. Accordingly, physiologically relevant models of human breast cancer that recapitulate these events are needed to study cancer biology and evaluate therapeutic agents. Here, we report the generation and utilization of the human breast cancer in mouse (HIM) model, which is composed of genetically engineered primary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(47 citation statements)
references
References 20 publications
1
45
0
1
Order By: Relevance
“…Such a model is reminiscent of colorectal cancer that may arise either through a polyp-dependent (adenoma carcinoma) process, or through a non-polyp-dependent (de novo) pathway associated with greater invasive and metastatic potential (Tanaka, 2009). In preclinical models of breast cancer, disruption of the TP53 pathway and/or constitutive activation of HER2, FAK or KRAS produce DCIS, but further inhibition of pRb signalling and/ or activation of the phosphatidylinositol 3 0 -kinase pathway appear necessary to promote malignant progression (Lightfoot et al, 2004;Golubovskaya et al, 2009;Wu et al, 2009). Comparative genomic hybridisation studies have also identified genetic pathways -for example through loss of genetic material of 16q associated with well-differentiated to intermediately differentiated DCIS and grade 1 IDC, or gains of 8q, 17q, and 20q associated with poorly differentiated DCIS and grade 3 IDC (Buerger et al, 2001) -that support a linear progression model for the transition from normal to DCIS to IDC.…”
Section: Discussionmentioning
confidence: 99%
“…Such a model is reminiscent of colorectal cancer that may arise either through a polyp-dependent (adenoma carcinoma) process, or through a non-polyp-dependent (de novo) pathway associated with greater invasive and metastatic potential (Tanaka, 2009). In preclinical models of breast cancer, disruption of the TP53 pathway and/or constitutive activation of HER2, FAK or KRAS produce DCIS, but further inhibition of pRb signalling and/ or activation of the phosphatidylinositol 3 0 -kinase pathway appear necessary to promote malignant progression (Lightfoot et al, 2004;Golubovskaya et al, 2009;Wu et al, 2009). Comparative genomic hybridisation studies have also identified genetic pathways -for example through loss of genetic material of 16q associated with well-differentiated to intermediately differentiated DCIS and grade 1 IDC, or gains of 8q, 17q, and 20q associated with poorly differentiated DCIS and grade 3 IDC (Buerger et al, 2001) -that support a linear progression model for the transition from normal to DCIS to IDC.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, ectopic expression of HGF and/or TGF-b in mouse fibroblasts before the implantation of ostensibly normal human mammary epithelial cells resulted in the outgrowth of benign and malignant lesions in the humanized fat pads of NOD/SCID mice (Kuperwasser et al, 2004;Wu et al, 2009). This suggests an important role of stromal fibroblast TGF-b in promoting breast carcinogenesis (Fig.…”
Section: Tgf-bmentioning
confidence: 99%
“…Using primary, noncancerous human epithelial cells, several human-in-mouse models of skin carcinoma, melanoma, and breast cancer have been developed in a similar fashion to study the cellautonomous roles of oncogenic events (Fan et al 1997;Khavari 2006;Wu et al 2009). In addition, microenvironmental influences in carcinogenesis have also been examined in a human mammary reconstitution system, where the mouse MFP of SCID mice is "humanized" by introducing human mammary fibroblasts, thus facilitating proper colonization and growth of human mammary epithelial cells in the chimeric stroma (Kuperwasser et al 2004).…”
Section: Human Tissue Recombination Strategies To Convert Benign Humamentioning
confidence: 99%